Kecemasan Kesehatan Remaja di Layanan Kesehatan Primer: Studi Kasus Intervensi CBT dan Early Improvement - Ardhito Dharma; Yanto Prasetyo; Rizki Maulana Hidayatullah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Health anxiety is a psychological condition characterized by excessive and persistent worry about having or developing a serious illness despite the absence of objective medical evidence. Among adolescents, health anxiety often manifests through recurrent somatic complaints that lead to repeated visits to primary health care services. This study aims to describe the dynamics of health anxiety in an adolescent and to examine the early response to a cognitive behavioral therapy (CBT) intervention delivered in a primary health care setting. This research employed a clinical case study design with a descriptive qualitative approach supported by quantitative assessment data. The participant was an adolescent presenting with recurrent physical complaints without identifiable medical pathology. Data were collected through clinical interviews, behavioral observation, and standardized psychological instruments, namely the Short Health Anxiety Inventory (HAI-18) and the Patient Health Questionnaire-15 (PHQ-15). Quantitative analysis focused on pre- and post-intervention score comparison, calculation of change scores, and the Reliable Change Index to evaluate individual-level change. The findings revealed a high level of health anxiety accompanied by low severity of somatic symptoms, indicating that psychological distress was primarily driven by maladaptive cognitive interpretations rather than physical pathology. Following the CBT intervention, a reduction in health anxiety scores was observed, reflecting an early improvement, although the change did not reach statistical significance based on the Reliable Change Index. These results suggest that CBT may produce meaningful early changes in health anxiety when implemented in primary health care settings, even with brief intervention formats. The study highlights the importance of early psychological assessment and intervention for adolescents with recurrent somatic complaints and supports the integration of mental health services within primary health care. However, findings should be interpreted cautiously due to the single-case design, and further research with larger samples and longitudinal follow-up is recommended